2013
DOI: 10.1177/1074248412472258
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib, a Small-Molecule Receptor Tyrosine Kinase Inhibitor, Suppresses Neointimal Hyperplasia in Balloon-Injured Rat Carotid Artery

Abstract: The migration and proliferation of vascular smooth muscle cells (VSMCs) induced by growth factors play a critical role in in-stent stenosis after percutaneous coronary intervention (PCI). The present study tested the hypothesis that sunitinib malate (sunitinib), a tyrosine kinase inhibitor of multiple receptors for growth factors, can reduce neointimal formation after arterial injury in vivo and sought to reveal the underlying mechanism in vitro. Male Wistar rats with balloon-injured carotid arteries were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…PDGF receptor tyrosine kinase inhibitors such as imatinib also showed an inhibitory effect on neointimal hyperplasia [33,34]. Sunitinib is a multi-target inhibitor of receptor tyrosine kinases including vascular endothelial growth factor (VEGF) receptor and PDGF receptor subtypes, so it could be a potential drug candidate for inhibition of neointimal hyperplasia [35,36]. Recently, Ishii et al reported that orally administered sunitinib significantly inhibited neointimal hyperplasia in balloon-injured rat carotid artery by reducing cell proliferation [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDGF receptor tyrosine kinase inhibitors such as imatinib also showed an inhibitory effect on neointimal hyperplasia [33,34]. Sunitinib is a multi-target inhibitor of receptor tyrosine kinases including vascular endothelial growth factor (VEGF) receptor and PDGF receptor subtypes, so it could be a potential drug candidate for inhibition of neointimal hyperplasia [35,36]. Recently, Ishii et al reported that orally administered sunitinib significantly inhibited neointimal hyperplasia in balloon-injured rat carotid artery by reducing cell proliferation [36].…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib is a multi-target inhibitor of receptor tyrosine kinases including vascular endothelial growth factor (VEGF) receptor and PDGF receptor subtypes, so it could be a potential drug candidate for inhibition of neointimal hyperplasia [35,36]. Recently, Ishii et al reported that orally administered sunitinib significantly inhibited neointimal hyperplasia in balloon-injured rat carotid artery by reducing cell proliferation [36]. Sanders et al introduced a PLGA perivascular bilayer wrap device for which sunitinib was used as a model drug [35].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the PDGFR signaling pathway in the pathophysiology of atherosclerosis and restenosis following angioplasty has been highlighted by recent studies (10,13,14). The potential to reverse in-stent restenosis through inhibiting this signaling pathway has been investigated (7,8,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…This agent exerts anticancer effects and has been widely used for the treatment of metastatic renal cell carcinoma and gastrointestinal stromal tumors (11,12). Previous studies have administered sunitinib orally to prevent restenosis in a balloon-injury carotid artery model (13). However, systemic administration of a PDGFR inhibitor requires a relatively high dose, which may cause adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of sunitinib, an angiogenesis inhibitor, was motivated by the presence of neovessels (Figure 1), and the expression of the growth factors PDGF, VEGF and their respective receptors (Figure 2) in the juxta-anastomotic NH lesions in our porcine AVG model. A recent study by Ishii et al reported that sunitinib inhibited PDGF-induced DNA synthesis, proliferation and migration in cultured HASMCs, and inhibited NH formation in a rat model of balloon-injury of carotid arteries (35). We previously showed that there was a significant difference between cultured arterial and venous SMCs in their response to the PDGFR inhibitor imatinib (36).…”
Section: Discussionmentioning
confidence: 99%